Atom site preference and γ′/γ mismatch strain in NiAlCoTi superalloys. (June 2016) - Oni, A.A.; Broderick, S.R.; Rajan, K.; LeBeau, J.M.
Abstract: The structure and chemistry of NiCoAlTi quaternary superalloys are investigated at the microstructural and atomic scale. Atom probe tomograghy (APT) is used to quantify phase compositions and elemental partitioning behavior. Using aberration corrected electron microscopy, the site occupancy of the atoms within the A3 B structure (L12 –type) γ ′ phase is determined via atomic resolution energy dispersive X-ray spectroscopy (EDX). Ni is observed to preferentially occupy the A sub-lattice positions for all alloys, while Al and Ti occupy the B sub-lattice. In contrast, Co's site preference changes from a random distribution to the A sub-lattice as the alloy composition changes, in agreement with theoretical predictions from literature. Finally, the lattice strain across the γ ′/ γ interfaces is measured as a function of alloy composition. Highlights: The structure and chemistry of NiCoAlTi quaternary superalloys are investigated at the microstructural and atomic scale. Atom probe tomograghy is used to quantify phase compositions and elemental partitioning behavior. We use electron microscopy to directly determine the site occupancies via atomic resolution energy dispersive X-ray spectroscopy. Co's site preference changes from a random distribution to the A sub-lattice as the alloy composition changes.